2006
DOI: 10.1080/01913120500406616
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Findings and Tumor Necrosis Factor-alpha and Intercellular Adhesion Molecule-1 Expression in Psoriasis Patients Before and After Oral Cyclosporin A Therapy

Abstract: Elevated levels of proinflammatory cytokines, including tumor necrosis factor-alpha, are found in skin lesions and plasma of patients with psoriasis. Clinical improvement of psoriasis with cyclosporin A treatment is accompanied by downmodulation of proinflammatory epidermal cytokines. In this study to determine the effects of cyclosporin A on the ultrastructural changes and tumor necrosis factor-alpha and intercellular adhesion molecule-1 expression in psoriasis, biopsy specimens before and after cyclosporin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The blistering and the breach in continuity in the BM observed in the present study, closely resemble ultrastructural changes that can be observed in the skin of patients with lupus erythematosus and in the skin of a mouse model of systemic lupus erythematosus (SLE) (MRL/l strain) (35)(36)(37)(38). Furthermore, in psoriatic skin lesions, the lamina densa can be interrupted, as observed in the SH2D2A )/) mice in the present study (39). In oral lichen planus, disturbances of the basal lamina, such as increased width of the lamina densa and loss of hemidesmosomes, can be seen (40,41).…”
Section: Discussionsupporting
confidence: 87%
“…The blistering and the breach in continuity in the BM observed in the present study, closely resemble ultrastructural changes that can be observed in the skin of patients with lupus erythematosus and in the skin of a mouse model of systemic lupus erythematosus (SLE) (MRL/l strain) (35)(36)(37)(38). Furthermore, in psoriatic skin lesions, the lamina densa can be interrupted, as observed in the SH2D2A )/) mice in the present study (39). In oral lichen planus, disturbances of the basal lamina, such as increased width of the lamina densa and loss of hemidesmosomes, can be seen (40,41).…”
Section: Discussionsupporting
confidence: 87%
“…Vessels were highly aberrant in the dermis of psoriatic skin 22 , 23 . Some researchers have proved that E-selectin CD54 and CD106 are over expressed in inflamed vasculature in psoriatic lesions 24 , 25 . In our experiment, in contrast with the pIL-4-DMSO application formula without RA, more significant reductions of the expression of these cell adhesion molecules were presented in the formula using RA-pIL-4-DMSO ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additional pharmacotranscriptomic approaches in the CsA treatment revealed the molecular reversion of several cytokine levels [ 58 , 59 ] and transforming growth factor (TGF)-β isoforms [ 60 ], with the former study further displaying the reduction of K16 + , CD3 + , and CD25 + cells in the lesional skin [ 58 ]. Furthermore, immunohistochemical staining for TNF and ICAM-1 of psoriatic skin was significantly reduced after CsA treatment approaching non-lesional levels [ 61 ].…”
Section: Traditional Therapiesmentioning
confidence: 99%